Damping of the track horizontal, transversal vibrations - V. M. Bel’kov (Вестник Научно-исследовательского института железнодорожного транспорта, 2020)
Knowledge of the oscillation process nature in horizontal plane across the track allows selecting the way of damping for reducing decrease of strength properties of polymer gaskets, rails, sleepers and earthworks under effect of horizontal vibrodynamic loads occurring during the rolling stock movement. Maximum horizontal deformation of polymer gaskets across the track does not exceed 10% therefore stress and deformation of polymer material can be done using the Hooke’s law.This is the first systematization of formulae for calculation of polymer gaskets, as well as the first resolution of the task when not pure shear takes place under effect of tangential stresses with simultaneous effect of vertical load. Damping coefficient of polyurethane gaskets is the same as for rubber gaskets; however, their service life is 2.5 times longer.Based on the presented physical mesomechanics it is demonstrated regarding the surface layer of two metal bodies contact under significant load that the surface mesolayer has damping properties, and vibrating oscillations occurring in the truck wheels when rolling stock moves on the rails will be reflected from the contact pad. The process of wheel and rail sliding in transversal direction is accompanied with increase of the total rolling friction and noise, elevated wear and tear of rails and wheel rims. In order to reduce transversal deformations and amplitude of the rails and sleepers torsion oscillations during rolling movement it is proposed to change the shape of polyurethane gaskets. Gaskets with variable thickness will more effectively reflect the shear transversal oscillating waves and reduce transversal forces.